Microsoft visual basic programs to accompany programming logic and design - Smith, Jo Ann (Cengage Learning, 2015)
The guide combines clear explanations of concepts and syntax with pseudocode, complete programming examples, numerous visuals, and real-world, business-related Visual Basic code examples. Students practice concepts with both lab exercises and revised practice opportunities in each section. The logic and pseudocode for many of the lab exercises has been developed and discussed in Joyce Farrell's textbook